Falsa interface como recurso poético na obra interativa - Sogabe, Milton Terumitsu [UNESP] (2014)
The concept of false interface is born of the observation and production of interactive installations mediated by digital technology. The false interface is not a technological interface that allows the public to interact with a digital system, but it is a poetic resource, generally an apparatus or craft object with which the public interacts with the artwork, which is a system. The false interface presents a physical relationship, a connection with the technological interface. The playfull audience relates with the false interface and technological interface goes unnoticed in the background, although it captures and send it to the system the public performance.